Assessment of Pesticide Biohazards in Neurodegenerative Diseases; Data Analysis Statistical Study - Marwan M. Merkhan; Zeina A. Althanoon; Ahmed A Mohammed; Ibrahim M. Faisal (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The initiation of late onset neurodegenerative diseases remains unknown. New researchessuggested that prolonged exposure to pesticides might lead to the initiation of neurodegenerative diseases,but the results were subject to controversy. Aims: The present study aimed to demonstrate an update dataminingto compare published data for studies comparing role of pesticide in induction of neurodegenerativediseases (Parkinson’s diseases, Alzheimer’s diseases, and Amyotrophic lateral sclerosis) Results: A clearassociation has been noticed across different studies regarding correlation between pesticide exposure andParkinson’s disease or Amyotrophic Lateral Sclerosis (Odd Ratio >1), nevertheless, the association wasweaker between exposure to pesticide and the development of Alzheimer’s disease (Odd Ratio close to 1)Conclusions: There is good quality evidence that the impact of pesticide in initiation of neurodegenerativedisease is statistically approved. However, there is inconclusive evidence from randomised controlledtrials to show significant induction of neurodegeneration. More research is needed particularly long-termcontrolled studies on laboratory animals.